Syncollin is required for efficient zymogen granule exocytosis - Wäsle, Barbara (Portland Press Ltd., 2005)
Syncollin is a 13 kDa protein that is present in the exocrine pancreas, where the majority of the protein is tightly attached to the luminal surface of the zymogen granule membrane. We have addressed the physiological role of syncollin by studying the phenotype of syncollin KO (knockout) mice. These mice show pancreatic hypertrophy and elevated pancreatic amylase levels. Further, secretagogue-stimulated amylase release from pancreatic lobules of syncollin KO mice was found to be reduced by about 45% compared with wild-type lobules, and the delivery of newly synthesized protein to zymogen granules was delayed, indicating that the mice have a pancreatic secretory defect. As determined by two-photon imaging, the number of secretagogue-stimulated exocytotic events in acini from syncollin KO mice was reduced by 50%. This reduction was accounted for predominantly by a loss of later, ‘secondary’ fusion events between zymogen granules and other granules that had already fused with the plasma membrane. We conclude that syncollin is required for efficient exocytosis in the pancreatic acinar cell, and that it plays a particularly important role in compound exocytosis.